The signature of local adaptations in human polymorphism data - Di Rienzo, Anna (Henry Stewart Talks, 2007)
Changes in habit and life style during human evolution, Evolutionary dynamics of neutral and advantageous mutations, Signature of natural selection on patterns of variation linked to an advantageous variant, Distinguishing between demography and natural selection, Duffy blood group locus, Lactase persistence, Skin pigmentation, Salt sensitivity variants and hypertension